Polish and Hungarian co-ooperation in acoustics in the last forty years - ILLÉNYI, Andràs (Archives of Acoustics, 1998)
The co-operation in acoustics was wide prosperous between the East Central European Countries in the second part of this century. Within the framework of this co-operation seems very fruitful and effective the collaboration typically between Hungarian and Polish acousticians and institutions.